2021
DOI: 10.1146/annurev-immunol-093019-122827
|View full text |Cite
|
Sign up to set email alerts
|

Immune System Investigation Using Parasitic Helminths

Abstract: Coevolutionary adaptation between humans and helminths has developed a finely tuned balance between host immunity and chronic parasitism due to immunoregulation. Given that these reciprocal forces drive selection, experimental models of helminth infection are ideally suited for discovering how host protective immune responses adapt to the unique tissue niches inhabited by these large metazoan parasites. This review highlights the key discoveries in the immunology of helminth infection made over the last decade… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 212 publications
1
26
0
Order By: Relevance
“…A safety study evaluating the effect of orally administered 2500 Trichuris suis eggs in 10 MS patients could not observe Trichuris suis ova-induced effects on disease progression (Table 2) (51, 336). In line, in this study there were no significant alterations detected regarding cytokine expression and T cell-specific transcriptions factors (336). A 9-month double-blind, randomized, placebo-controlled study enrolling 71 RRMS patients investigated the effect of transcutaneous application of hookworm larvae on lesion burden (Table 2) (50).…”
Section: Therapeutic Targetsmentioning
confidence: 57%
See 3 more Smart Citations
“…A safety study evaluating the effect of orally administered 2500 Trichuris suis eggs in 10 MS patients could not observe Trichuris suis ova-induced effects on disease progression (Table 2) (51, 336). In line, in this study there were no significant alterations detected regarding cytokine expression and T cell-specific transcriptions factors (336). A 9-month double-blind, randomized, placebo-controlled study enrolling 71 RRMS patients investigated the effect of transcutaneous application of hookworm larvae on lesion burden (Table 2) (50).…”
Section: Therapeutic Targetsmentioning
confidence: 57%
“…Under treatment, there was a reduction of new GELs by 70% compared to baseline with a return to baseline after two months of follow-up. The reduction of lesions was also associated with increased serum levels of of IL-4 and IL-10 in 80% of the participants (336). The follow-up study including 16 RRMS patients also showed a trend of reduction of active MRI lesions compared to baseline (344).…”
Section: Therapeutic Targetsmentioning
confidence: 72%
See 2 more Smart Citations
“…Long asymptomatic phase typically associated with these infections has given rise to the idea of “helminth therapy” oriented toward suppression of inflammation in hyperinflammatory immune diseases. While multiple excretory/secretory (ES) factors have been reported to exhibit immune modulatory properties, the mechanisms underlying their effect on specific cell types remain largely obscure, with most of the studies focusing on Th2 responses and macrophage polarization 27 . The recent recognition of neutrophils as major players in host immunity to helminth infections has brought into focus the role of NETs in anti-parasitic responses 28 .…”
Section: Discussionmentioning
confidence: 99%